2010
DOI: 10.1016/j.engstruct.2010.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Coupled and uncoupled nonlinear elastic finite element models for monotonically loaded sheathing-to-framing joints in timber based shear walls

Abstract: a b s t r a c tFour different elastic models for sheathing-to-framing connections are presented and evaluated on a single connection level and on a shear wall level. Since the models are elastic in their nature they are suitable mainly for cases where the sheathing-to-framing connections are subjected to monotonically increasing displacements. Of the four models one is uncoupled and the others are coupled with respect to the two perpendicular displacement directions in a two-dimensional model. Two of the coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Aimed at improving the structural behaviour of wood shear walls, more attention has been paid to the lateral resistance of individual sheathing-to-framing joints. It is commonly accepted that the strength and stiffness performance of shear walls are decided mainly by the joint characteristics (Vessby et al 2010). Lam et al (1997) found a substantial increase in both strength and stiffness in shear walls when nonstandard large dimension OSB panels were used.…”
Section: Introductionmentioning
confidence: 99%
“…Aimed at improving the structural behaviour of wood shear walls, more attention has been paid to the lateral resistance of individual sheathing-to-framing joints. It is commonly accepted that the strength and stiffness performance of shear walls are decided mainly by the joint characteristics (Vessby et al 2010). Lam et al (1997) found a substantial increase in both strength and stiffness in shear walls when nonstandard large dimension OSB panels were used.…”
Section: Introductionmentioning
confidence: 99%
“…For discussions of other more sophisticated monotonic loading models, see e.g. Judd and Fonseca [10] and Vessby et al [11], where e.g. models for mixed-mode loading are discussed.…”
Section: Different Fe Models For Sheathing-to-framing Jointsmentioning
confidence: 99%
“…In practise, fasteners are most often simulated with springs or with extra layers to which special material characteristics, simulating actual situation, are attributed. The most accurate way of modelling timber-framed walls using the finite element method (FEM) has been used by many researchers; see for example Ayoub [9], He et al [10], Vessby et al [11], Tarabia and Itani [12], Foschi [13] and Falk and Itani [14]. The FEM modelling of timber-framed walls was also presented in Kozem Šilih et al [15], where timber frame was simulated with line elements, sheathing boards with shell elements and staples with spring elements.…”
Section: Computational Modelsmentioning
confidence: 99%